2014
DOI: 10.1002/asia.201402645
|View full text |Cite
|
Sign up to set email alerts
|

Melamine as an Effective Supramolecular Modifier and Stabilizer in a Nanotube‐Constituted Supergel

Abstract: Self-assembly of N-fluorenyl-9-methoxycarbonyl glutamic acid (Fmoc-Glu) in water generates metastable single-wall nanotubes. These nanotubes entangle and bundle together to form unstable gels that shrink with time and finally result in lamellar crystalline precipitates. Melamine (Mm) was employed as a supramolecular modifier and stabilizer to improve the stability of the nanotubes. Mm interacts with the carboxyl-rich surfaces of the nanotubes via H-bonds and static electronic forces to diminish the high affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 95 publications
7
32
1
Order By: Relevance
“…7 indicating the presence of inter-carboxylic acid hydrogen bonding. [31][32][33] In contrast to that, the free C=O stretching vibration peak appeared at 1690 cm -1 is comparatively small. In addition, peaks located at 1630 cm -1 as well as 1543 cm -1 are contributed by the amide I and amide II bands, confirming the existence of amide-amide hydrogen bonding.…”
Section: Resultscontrasting
confidence: 58%
“…7 indicating the presence of inter-carboxylic acid hydrogen bonding. [31][32][33] In contrast to that, the free C=O stretching vibration peak appeared at 1690 cm -1 is comparatively small. In addition, peaks located at 1630 cm -1 as well as 1543 cm -1 are contributed by the amide I and amide II bands, confirming the existence of amide-amide hydrogen bonding.…”
Section: Resultscontrasting
confidence: 58%
“…The slight shifts may be derived from the alternation of particle sizes and the tiny change of UV/Vis absorbance. Upon increasing molar ratio of Mm, it was found that the Cotton effects were inversed only after adding 2 equivalent or more Mm (Figure S7 in the Supporting Information), indicating that two carboxylic acids of glutamic acid moiety must be occupied to trigger the helicity inversion . This speculation was then confirmed by the TEM studies (Figure S8 in the Supporting Information), showing that, when the ratio of Mm was lower than 2 equivalents, only belts without apparent chirality were formed, while the twisted topology appeared after adding more than 2 equivalents of Mm.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of these developments, the effect of amino acid type or α‐substituent structure on multicomponent self‐assembly is still poorly understood. Unlike strong binding interaction between amino acids and other components, relatively weak binding could be significantly influenced by self‐sorting competition, which might result in a selectivity in various types of amino acid residues upon the coassembly with a weak binder. Thus, a better understanding of the effect is of vital importance in designing amino acid/short peptide‐based multicomponent materials with desired functions.…”
Section: Methodsmentioning
confidence: 99%
“…Clearly, the complexation with bipyridine enhances the growth of Gly backbone in 3D scale rather than 1D. [27b] The self‐assembly between Gly and BP was also studied by small and wide angle X‐ray scattering (SAXS and WAXS) techniques as shown in Figure d. The pristine Gly assembly in water showed the first‐order peak at 0.33 Å −1 ( d = 1.9 nm), which gradually disappeared when 0.5 molar equivalent BP was added, in a good agreement with the molar ratio of 2:1 revealed by single crystal analysis.…”
Section: Methodsmentioning
confidence: 99%